Aplicacion de electroforesis capilar para la caracterizacion de gliadinas de trigos argentinos - Colombo, A.=700 1 Ribotta, P.D.; Leon, A.E.
(Es, En)
ilus., 33 ref.
Keywords: TRIGO; PROLAMINAS; AELECTROFORESIS; ARGENTINA; AGRISCENTIA